The Mechanism of HPV-mediated DNA Methylation in the Promoter Region of Long-chain Non-coding RNA MAGI2-AS3 in the Occurrence and Development of Cervical Cancer - Jie Zhang; Qiong Xia; Qinghua Zhang (IMR Press, 2024)
Background: Cervical cancer, a malignancy of gynecological origin, typically necessitates a therapeutic approach combining surgery and chemoradiotherapy as the primary intervention. However, the 5-year survival rate remains suboptimal, prompting researchers to explore novel strategies for the early diagnosis and treatment of cervical cancer. This study delves into the investigation of human papillomavirus (HPV)-mediated DNA methylation modifications within the promoter region of the long non-coding RNA MAGI2-AS3 during cervical cancer development. This paper is an experimental study, laboratory based, using cell lines. Methods: A lentivirus overexpression vector encoding HPV16 E6/E7 proteins was established for transfecting cervical epithelial cells. The methylation status of DNA in the MAGI2-AS3 promoter region was assessed using MassARRAY, and the MAGI2-AS3 gene expression was measured through quantitative real time polymerase chain reaction (qRT-PCR). Subsequently, the correlation between methylation levels and gene expression in cervical cancer was analyzed. Results: (1) Relative to the HPV-negative cervical cancer cell line C33A, MAGI2-AS3 expression significantly decreased in the HPV-positive cervical cancer cell line Siha. (2) The methylation rate of 16 CpG sites in the HPV-positive cervical cancer cell line Siha was notably higher compared to the HPV-negative cervical cancer cell line C33A. (3) To further substantiate the regulatory impact on DNA methylation and expression within the MAGI2-AS3 promoter region, we silenced the expression of HPV16 E6 in the HPV-positive cervical cancer cell line Siha using HPV16 E6 siRNA. The ensuing qRT-PCR analysis revealed a significant up-regulation of MAGI2-AS3 expression in the HPV16 E6 siRNA group when contrasted with the negative control group. MassARRAY analysis was employed to gauge the DNA methylation levels in the promoter region of the MAGI2-AS3 gene in HPV-positive cervical cancer cells (Siha) following HPV16 E6 silencing. The results demonstrated a significantly lower methylation rate at the CpG_29 site in the HPV16 E6 siRNA group compared to the HPV16 E6 siRNA group. Conclusions: The study establishes a close association between HPV infection and elevated methylation levels coupled with diminished expression of MAGI2-AS3. The influence of HPV infection on the malignant transformation of cervical epithelial cells is potentially mediated through the regulatory modulation of MAGI2-AS3 expression via DNA methylation.